An Analysis of English Teacher's Classroom Management at SMKN 3 Padang - Ayuni Putri; Aryuliva Adnan (Universitas Negeri Padang, 2020)
This research aimed to analyze the typical classroom management of an English teacher in a vocational high school in Padang. The sample of this research was two English teachers, teacher A, and teacher B. They taught the tenth-grade students, once a week, for 3x45minutes. The data were analyzed by using the theory of Wright and collected by taking video and field notes. This study limited the day to gain the data in six days. Finally, it showed that teachers in SMK 3 Padang were having a different style of classroom management personally, and found was a teacher in SMKN 3 Padang has issue in time management and discipline.